2011
DOI: 10.1007/978-3-642-17214-4_7
|View full text |Cite
|
Sign up to set email alerts
|

Nampt and Its Potential Role in Inflammation and Type 2 Diabetes

Abstract: Nicotinamide phosphoribosyltransferase Nicotinamide phosphoribosyltransferase (Nampt Nampt ) is a key nicotinamide adenine dinucleotide (NAD) NAD biosynthetic enzyme in mammals, converting nicotinamide nicotinamide into nicotinamide mononucleotide nicotinamide mononucleotide (NMN NMN ), an NAD intermediate. First identified in humans as a cytokine cytokine pre-B-cell colony enhancing factor pre-B cell colony enhancing factor (PBEF PBEF ) and subsequently described as an insulin-mimetic hormone visfatin visfati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 103 publications
0
26
0
2
Order By: Relevance
“…By microarray analysis, the transcript of ALDH2 were found to be down-regulated during the fibrogenesis process and potential used as novel serum markers of fibrosis21. NAMPT is a key nicotinamideadenime dinucleotide (NAD) biosynthetic enzyme in mammals, it has recently excited the scientific interest of researchers from diverse fields, including NAD biology, metabolic regulation and inflammation22. However, the top of enriched biological function categories of down-regulated proteins in reverted HSCs was cytoskeleton organization process (15) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…By microarray analysis, the transcript of ALDH2 were found to be down-regulated during the fibrogenesis process and potential used as novel serum markers of fibrosis21. NAMPT is a key nicotinamideadenime dinucleotide (NAD) biosynthetic enzyme in mammals, it has recently excited the scientific interest of researchers from diverse fields, including NAD biology, metabolic regulation and inflammation22. However, the top of enriched biological function categories of down-regulated proteins in reverted HSCs was cytoskeleton organization process (15) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These inhibitors have not only been instrumental in the study of this enzyme and NAD homeostasis in general, but they also have potential as anticancer agents. NamPRT levels are significantly increased in a number of tumours 64,112 , and NamPRT has been implicated in vasculogenesis 113 and inflammation 22,114 . Thus, targeting NamPRT in cancer patients is expected to bring about pleiotypic antitumour effects in addition to direct impairment of cancer cell metabolism (FIG.…”
Section: Nature Reviews | Cancermentioning
confidence: 99%
“…Recent studies have demonstrated controversial findings regarding an association of vistafin level with BMI, insulin, glucose, hs-CRP, or HOMA-IR [15,37,38]. Because serum level of vistafin in non-CV complicated T2DM patients was higher than in diabetics with known CV disease [39], it has been suggested that vistafin might have a positive effect of repair system and prevent of microvascular and macrovascular complications [17].…”
Section: Diabetes-induced Epc Dysfunction Is a Critical Factor In Micmentioning
confidence: 99%